PEMBERDAYAAN KELOMPOK WANITA TANI DALAM DIVERSIFIKASI OLAHAN IKAN NILA - Putri, Diah Asta; Pratiwi, Ambar; Suwartiningsih, Nurul (Universitas Ahmad Dahlan, Yogyakarta, 2018)
Communities in the area of PRA Ambarketawang and KWT An-Naba’ Gamping Sleman Yogyakarta conduct tilapia fish cultivation. But, they usually sell tilapia fish to the market in raw condition. Therefore, we intends to provide counseling, training and assistance in diversifying the processing of tilapia fish. This activity is an effort to fulfill the needs of protein for daily consumption from ingredients cultivated by the local community. This activity can also be useful in increasing the selling power of tilapia fish and increasing income. The activities carried out in several sessions included counseling on the benefits, nutritional content and potential of tilapia, training in making nuggets, noodles, fish sticks, meatballs, training on product packaging and product marketing. The conclusion of this service activity is the increasing knowledge and skills of partners in processing tilapia into products in the form of fish nuggets, fish sticks, fish noodles and fish meatballs and increasing partners knowledge in packaging products safely and attractively in order to compete with other similar products. Keywords: tilapia, nugget, meatball, noodle, fish stick